Efeito neuroprotetor do α-bisabolol em camundongos submetidos á isquemia cerebral focal permanente - Fernandes, Mara Yone Soares Dias (2015)
Stroke is the leading cause of mortality in Brazil, affecting about 200,000 individuals annually. The pathophysiology of ischemic stroke involves a complex cascade of events such as inflammation and oxidative stress which will lead to neuronal death and cognitive deficits. The α-bisabolol is a sesquiterpene alcohol, natural, monocyclic, found as main constituents of the essential oil of Matricaria chamomilla, which has anti-inflammatory, antioxidant and anti-apoptotic already described. To evaluate the neuroprotective effects of this compound in mice underwent permanent occlusion of the middle cerebral artery (pMCAO), the animals were pre and post treated with α-bisabolol at doses of 50, 100 and 200 mg / kg, orally for 24, 48, 72, 96 or 120 hours after pMCAO. The animals were evaluated 24 hours after ischemia to verify the area of ischemic damage, and neurological evaluation and myeloperoxidase activity. Seventy-two hours after pMCAO, the locomotor activity tests, working memory and aversive recent memory were performed. Ninety six hours after the pMCAO was performed the object recognition test, and the animals were euthanized for carrying out the immunohistochemistry for TNF-α, iNOS and GFAP and for histology analyes Cresil violet and Fluoro Jade C. Finally, 120 h after pMCAO, the spatial memory was evaluated. The α-bisabolol reduced significantly ischemic damage and neurological deficit and normalized the locomotor activity. The α-bisabolol showed protection against the deficits in working, spatial, object recognition and aversive memories. The α-bisabolol (200 mg / kg) significantly prevented the increase of MPO and TNF-α in the temporal cortex and the increased of iNOS both in the temporal cortex and in striatum. Also prevented the increase in astrogliosis in there area. The α-bisabolol (200 mg / kg) showed protection against neuronal death. The results of this study showed that α-bisabolol has neuroprotective activity probably due to its anti-inflammatory action, but other mechanisms can not be discarded.